Morphology, phylogeny and taxonomy of Amolops ricketti (Amphibia, Ranidae) in Guizhou Province - XIAO Ning; LUO Qinghua; DENG Huaiqing; ZHOU Jun; LUO Tao (浙江大学学报. 农业与生命科学版)
Fourteen specimens of Amolops ricketti collected in Guizhou Province were compared with the groups from A. ricketti, based on the analysis of morphology and mitochondrial 16S rRNA and COI sequence. The results showed that the different local populations of A. ricketti from Guizhou Province had the similar morphological characters with the species of A. sinensis, and the average genetic distances between the local populations of A. ricketti from Guizhou Province and A. sinensis (type locality: Shimentai Nature Reserve, Guangdong) were 0.74%-1.30%, and that of A. ricketti (type locality: Mt. Wuyi, Fujian) were 6.82%-6.96%. Meanwhile, a phylogenetic tree constructed based on the mitochondrial joint sequence showed that A. ricketti from Guizhou Province and A. sinensis (type locality: Shimentai Nature Reserve, Guangdong) were clustered a clade. Therefore, the original records of A. ricketti in the northern part (Xishui, Kuankuoshui), the central part (Huangping, Majiang), the eastern part (Jiangkou), the southeast part (Leigongshan, Danzhai) of Guizhou Province should be revised to A. sinensis. These origins represent the distribution of the previous records of A. ricketti in Guizhou, and it is proposed to amend the A. ricketti distributed in Guizhou Province to A. sinensis. It was indicated that the differentiation of A. sinensis local populations in the north, west, and south of the Wujiang River was related to the geographical barrier of Wujiang River system, and it should be further resolved.